Investigating the Effect of Using Waste Ultra-high-molecular-weight Polyethylene on the Fatigue Life of Asphalt Mixture - Hamedi, Gholam Hossein; Hadizadeh Pirbasti, Mohammad; Ranjbar Pirbasti, Zahra (Periodica Polytechnica Civil Engineering, 2020)
One of the effective parameters in the occurrence of fatigue cracking distress is the asphalt binder properties used, which must be controlled by appropriate asphalt binder or additives. In this study, the effect of using Ultra-High-Molecular-Weight Polyethylene (UHMWPE) was investigated on the fatigue cracking potential of asphalt mixtures. Two types of aggregates, asphalt binder performance grade (PG) 64-16, and UHMWPE additive in two percent of the asphalt binder were used in this study, which were tested at two temperatures and five different stress levels. Marshall mix design and indirect tensile fatigue test (ITFT) were used to determine the optimum content of the asphalt binder and the fatigue life of asphalt mixtures, respectively. The results of this study indicated that the application of polymer additives increased the fatigue life of the asphalt mixtures. The fatigue life of specimens made with granite aggregates was longer than those made with limestone aggregates, and the increased life due to the use of UHMWPE was longer in samples made with granite aggregates. As expected, increasing in temperature and stress levels reduced the fatigue life of the asphalt mixtures. This decrease was much lower in samples made of asphalt binder modified with polymeric materials than in control samples.